Penerapan Lean Six Sigma untuk Meningkatkan Keselamatan Pasien (Patient Safety) di Rumah Sakit - Meutya Zahra Saphira; Nadya Nur Syafina Putri; Acim Heri Iswanto (Yayasan Citra Dharma Cindekia, 2026)
Patient safety is a core pillar of quality healthcare and remains a global challenge in hospital settings. Lean Six Sigma (LSS) is a process improvement methodology that integrates Lean principles to eliminate waste and Six Sigma tools to reduce variation and defects, offering significant potential for improving patient safety outcomes. This literature review aims to synthesize evidence on the application of Lean Six Sigma strategies in hospital environments and their impact on patient safety indicators. A systematic search was conducted across electronic databases including PubMed, Google Scholar, and Scopus using keywords such as